Femtosecond filamentation induced particles and their cloud condensation nuclei activity. (1st June 2019) - Ran, L.; Deng, Z.Z.; Ju, J.J.; Sun, H.Y.; Liu, J.S.; Lin, W.L.; Tian, P.; Liu, Q.; Huang, M.Y.; Wang, P.C.; Xia, X.A.; Pan, W.L.; et al.
Abstract: Laboratory experiments were conducted to investigate femtosecond filamentation induced particle formation and growth in particle-free air as well as in the presence of pre-existing ammonium sulfate aerosols. The ability of laser induced particles to act as cloud condensation nuclei (CCN) was explored. The influence of water vapor and the pulse energy on the production efficiency and activation properties of particles were also examined. In particle-free air, laser filaments could lead to a significant production of new particles, the number concentration of which was comparable to or larger than that in polluted ambient air, depending upon the pulse energy and humidity. Total particle number and mass concentrations within 20–708 nm were predominantly contributed by particles with a diameter smaller than 100 nm. Remarkably high NOx up to an order of ∼10 1 ppm was generated in the chamber, allowing sufficient production of HNO3 and probably subsequent HNO3 -H2 O binary nucleation. In the presence of pre-existing particles, the yield of particle number was largely enhanced in laser filaments, especially in humid air. Particle number size distribution shifted towards smaller particle size, leading to a slight increase in particle mass. It was found that a considerable portion of laser induced particles, no matter generated with or without pre-existing particles, could act as CCN. The amount of CCN at 0.80% supersaturation was in the magnitude of 10 4 ∼10 5 cm −3 in all experiments, nearly one order larger than the average ambient level even in severely polluted regions. Overall, increasing the pulse energy and water vapor would favor particle formation and growth as well as the production of CCN. Raising the pulse energy also resulted in a decline of the hygroscopic parameter κ, implying the modification of aerosol chemical composition. Though more investigative studies are still needed to explore mechanisms underlying some of these experimental results, laser filaments are undoubtedly capable of inducing substantial particle formation and modifying microphysical/chemical properties of pre-existing particles. By influencing these crucial properties and thereby aerosol direct/indirect climatic and environmental effects, laser filamentation would provide a promising potential for related atmospheric applications. Highlights: Femtosecond filamentation induced a significant production of gases and particles. Microphysical/hygroscopic properties of pre-existing particles were modified. Laser induced particles provided abundant cloud condensation nuclei. Increasing the pulse energy and water vapor would favor gas/particle production.